'Free to act by your own lights': Agency and Predestination in Marilynne Robinson's Gilead Novels. (15th March 2021) - Mouw, Alex
Abstract: This article explores Marilynne Robinson's attempt to reconcile the doctrine of predestination with a commitment to human agency by reading her novels Gilead, Home, Lila, and Jack alongside their intertextual companion, John Calvin. I argue that, rather than attempting to penetrate the enigma of predestination and agency through theological treatises, Robinson embodies the tension between them in fiction. Rather than defining a solution to the problem, she meaningfully charts the lived experience of it. Indeed, in the Gilead novels the experience of agency is itself agency within a universe defined by God's omnipotence. At the same time, characters' freedom to act otherwise than habit or impulse would dictate depends on right perception. Robinson's unique contribution to an American literary and theological legacy is to animate these tensions as only fiction can. Her novels offer a theological vista that cannot be separated from their fictional content, and so things that seem like tautologies grow profound through narration.